The Hello, Goodbye Window - Juster, Norton, 1929-; Raschka, Christopher ([New York] : Hyperion Books for Children, 2005)
The kitchen window at her grandparents' house is a magic gateway for one imaginative little girl.
"Michael di Capua books."
Keywords: Grandparent and child -- Fiction; Windows -- Fiction